Integration of TAM and MOOC for e-learning purpose - Tawafak R.M.; Romli A.; Malik S.I.; Alfarsi G. (American Institute of Physics Inc., 2023)
many studies looking at MOOC as a system actual of use. The main problem is the weakness of the system intention to use e-learning application systems. This study aims to develop the original TAM model by examining the TAM factors and MOOC platform for system actual use. The paper develops an adapted TAM with four additional factors of course content and interactivity with the new positive relationship among these constructs. The survey questionnaire was distributed to the prospective 307 respondents were received back with only 295 completed samples were deemed valid to proceed with this study. The technique is utilized with Al-Buraimi College in the academic department of scientific sections. There are 12 constructs tested in this study with results indicates the significant positive effect on the relationships proposed in the framework. Next, the data was coded and translated from paper into the PLS program. 2021 American Institute of Physics Inc.. All rights reserved.